Adhesion of gram‐negative rod‐shaped bacteria on 1D nano‐ripple glass pattern in weak magnetic fields. Issue 2 (24th May 2018) - Saleem, Iram; Masood, Samina; Smith, Derek; Chu, Wei‐Kan
Abstract: This research project has major applications in the healthcare and biomedical industries. Bacteria reside in human bodies and play an integral role in the mechanism of life. However, their excessive growth or the invasion of similar agents can be dangerous and may cause fatal or incurable diseases. On the other hand, increased exposure to electromagnetic radiation and its impact on health and safety is a common concern to medical science. Some nanostructure materials have interesting properties regarding facilitating or impeding cell growth. An understanding of these phenomena can be utilized to establish the optimum benefit of these structures in healthcare and medical research. We focus on the commonly found rod‐shaped, gram‐negative bacteria and their orientation and community development on the cellular level in the presence of weak magnetic fields on one dimensional nano‐ripple glass patterns to investigate the impact of nanostructures on the growth pattern of bacteria. The change in bacterial behavior on nanostructures and the impact of magnetic fields will open up new venues in the utilization of nanostructures. It is noticed that bacterial entrapment in nano‐grooves leads to the growth of larger colonies on the nanostructures, whereas magnetic fields reduce the size of colonies and suppress their growth. Abstract : Growth of rod‐shaped gram‐negative bacterial strains were studied on one dimensional nano‐ripple glass surface, fabricated by gas cluster ion beam irradiation and compared with the plain glass surface under similar conditions. Adhesion of bacteria and the growth patterns were clearly distinguishable between the plain surface and the nanostructure. Difference in bacterial growth and distribution was observed in the presence of weak magnetic field as well. We use different configurations (uniform and nonuniform) of magnetic fields to study the growth of rod‐shaped Escherichia coli and Pseudomonas aeruginosa on nano‐ripple glass. Bacterial colonies were larger on nano‐ripple glass but magnetic field suppresses the growth resulting in to smaller colonies.